Polyoxometalates as antitumor agents: Bioactivity of a new polyoxometalate with copper on a human osteosarcoma model - Leon, Ignacio Esteban (2014)
Polyoxometalates (POMs) are early transition metal oxygen anion clusters. They display interesting biological effects mainly related to their antiviral and antitumor properties. On the other hand, copper compounds also show different biological and pharmacological effects in cell culture and in animal models. We report herein for the first time, a detailed study of the mechanisms of action of a copper(II) compound of the group of HPOMs with the formula K7Na3[Cu4(H2O)2(PW9034)2]20H2O (PW9Cu), in a model of human osteosarcoma derived cell line, MG-63. The compound inhibited selectively the viability of the osteosarcoma cells in the range of 25–100 lM (p < 0.01). Besides, we have clearly shown a more deleterious action of PW9Cu on tumor osteoblasts than in normal cells. Cytotoxicity studies also showed deleterious effects for PW9Cu. The increment of reactive oxygen species (ROS) and the decrease of the GSH/ GSSG ratio were involved in the antiproliferative effects of PW9Cu. Moreover, the compound caused cell cycle arrest in G2 phase, triggering apoptosis as determined by flow cytometry. As a whole, these results showed the main mechanisms of the deleterious effects of PW9Cu in the osteosarcoma cell line MG-63, demonstrating that this compound is a promissory agent for cancer treatments.